Participial systems in Uralic languages: an overview - Ksenia Shagal (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2018)
This paper is an intragenetic typological study of participial systems in Uralic languages, a family demonstrating a significant degree of variation in this domain. The classification of participial forms is based primarily on two parameters, participial orientation, or relativizing capacity, and tense-aspect-modality (TAM). The sample comprises ten languages, and the data comes from descriptive studies as well as from native speakers and language experts. The study shows that participial systems in Uralic languages fall into three major groups, namely languages with inherently oriented participles, languages with contextually oriented participles, and languages featuring a combination of these participial types. The geographical distribution of participial systems shows strong areal tendencies resulting from language contact. For several centuries, western Uralic languages (e.g. Finnish and Hungarian) have been influenced by Slavic, Germanic and Baltic varieties, while eastern Uralic languages (e.g. Tundra Nenets and Khanty) historically form a linguistic area with northern Eurasian languages, such as Turkic and Yeniseian. As a result, the western varieties belong to the Standard Average European type with respect to participial properties, while the eastern ones make use of prenominal participial relative clauses, which are a well-known areal feature in North Asia. It is also noteworthy that Uralic languages do not show any clear matter borrowing in participial forms, so it is rather the pattern that is transmitted via contact. Аннотация. Ксения Шагал: Системы причастий в уральских языках: предварительный обзор. Данная статья представляет собой внутригенетическое типологическое исследование систем причастий в уральской языковой семье, которая отличается заметным разнообразием в этой области. Предлагаемая классификация причастных форм основана на двух основных параметрах: ориентации причастий и их видо-временных характеристиках. Изучаемая выборка включает в себя десять языков. Данные были получены в ходе работы ...